A função sócio-ambiental da propriedade urbana e as áreas de preservação permanente: a proteção das águas no ambiente urbano do município de Fortaleza - Paula, Tereza Emília Lima de (2007)
The institute of the property, throughout the centuries, suffered innumerable alterations to follow the modifications suffered in the society. Appearing as right basic in a first generation, enhancing the individuality and its limitless use, where the absolute power exerted by the owner prevailed, what guarantee the use, the enjoyment of the property of unquestioned form. Through the posterior generations of the basic rights, it guaranteed new dimensions, adjusting itself it the sprouting of new rights, incorporating in its essence social character e, to the end, in one third generation, ambient values, represented for the right to a healthful environment, with guarantee for the gifts and the future generations of a half healthful and balanced environment, for the sustainable development, presenting the urban property partner-ambient function. The areas of permanent preservation appear as limitation to the right of property, guaranteeing the ecological balance in urban environments. Delimited for the Forest Code, they are hosted by the Federal Constitution. Its reception must be found in the Municipal Managing Plans, indispensable instrument for the development and growth of the urban centers. In this direction, the fiscalization of these protected areas will fit to the City of Fortaleza, as the observance of the same ones in the Municipal Managing Plan, guaranteeing a healthful environment for everybody. By methodological option it was determined to impose a fine on bibliographical research, of elucidative nature, restricting it ambient problems in an only city, of Fortaleza, even so considering general presentations of the effective national legislation.